STUDY OF STRUCTURAL CHANGES IN ALLERGIC RHINOSINUSITIS (Medical science of Uzbekistan, 2023)
This study provides an in-depth analysis of the histological changes characterized in the context of allergic rhinosinusitis. The work focuses on structural adaptations of the nasal and sinus mucosa in response to chronic exposure to allergens. Thickening of the epithelial layer, metaplasia and hyperplasia of glandular cells, as well as damage to the basement membrane are examined in detail. Important attention is also paid to inflammatory infiltrates, including eosinophils, lymphocytes and monocytes. The results of the study not only expand the understanding of the pathogenesis of allergic rhinosinusitis, but also provide the basis for the development of more precise diagnostic and therapeutic strategies aimed at preserving the structural and functional integrity of the tissues of the upper respiratory tract. This work has implications for clinicians, researchers, and respiratory medicine professionals seeking to improve the diagnosis and treatment of allergic rhinosinusitis.